Phosphinothiolates as Ligands for Polyhydrido Copper Nanoclusters. Issue 49 (24th October 2014) - Huertos, Miguel A.; Cano, Israel; Bandeira, Nuno A. G.; Benet‐Buchholz, Jordi; Bo, Carles; van Leeuwen, Piet W. N. M.
Abstract Invited for the cover of this issue is the group of Piet W. N. M. van Leeuwen at the Institute of Chemical Research of Catalonia (ICIQ), Tarragona, Spain. The cover was designed by Miguel and the sun represents the photoactivity of the complex, resulting in the production of hydrogen. Read the full text of the article at 10.1002/chem.201404763.